Initial PCV Chemotherapy Followed by Radiotherapy Is Associated With a Prolonged Response But Late Neurotoxicity in 20 Diffuse Low-Grade Glioma Patients - Blonski, Marie; Obara, Tiphaine; Brzenczek, Cyril; Pouget, Celso; Dillier, Céline; Meyer, Mylène; Lavigne, Laura; Forthoffer, Natacha; Broussois, Aurélie; Gauchotte, Guillaume; Baron, Marie-Hélène; Rech, Fabien; et al. (Frontiers in Oncology, 2022)
Background Study RTOG 9802 in high-risk diffuse low-grade gliomas (DLGGs) showed the potential synergistic effect on survival of the procarbazine, CCNU, and vincristine (PCV) radiotherapy (RT) combination. Limited data on long-term neurocognitive impact and quality of life (QoL) have yet been reported. Patients and Methods We described a monocentric series of patients treated at first line by the combination of PCV immediately followed by RT between January 01, 1982 and January 01, 2017. Radiological data were collected and included volume, velocity of diametric expansion (VDE), and MRI aspects. Long-term neurocognitive and QoL were analyzed. Results Twenty patients fulfilled the eligibility criteria. The median response rate was 65.1% (range, 9.6%–99%) at the time of maximal VDE decrease corresponding to a median volume reduction of 79.7 cm3 (range, 3.1 to 174.2 cm3), which occurred after a median period of 7.2 years (range, 0.3–21.9) after the end of RT. An ongoing negative VDE was measured in 13/16 patients after the end of RT, with a median duration of 6.7 years (range, 9 months–21.9 years). The median follow-up since radiological diagnosis was 17.5 years (range, 4.8 to 29.5). Estimated median survival was 17.4 years (95% CI: 12; NR). After a long-term follow-up, substantial neurotoxicity was noticed with dementia in six progression-free patients (30%), leading to ventriculo-peritoneal shunt procedures in three, and premature death in five. Thirteen patients (65%) were unable to work with disability status. Successive longitudinal neurocognitive assessments for living patients showed verbal episodic memory deterioration. Conclusions PCV-RT combination seems to have not only an oncological synergy but also a long-term neurotoxic synergy to consider before initial therapeutic decision.